2018
DOI: 10.1088/1752-7163/aa8f7f
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive volatile metabolic fingerprinting of bacterial and fungal pathogen groups

Abstract: The identification of pathogen-specific volatile metabolic 'fingerprints' could lead to the rapid identification of disease-causing organisms either directly from ex vivo patient bio-specimens or from in vitro cultures. In the present study, we have evaluated the volatile metabolites produced by 100 clinical isolates belonging to ten distinct pathogen groups that, in aggregate, account for 90% of bloodstream infections, 90% of urinary tract infections, and 80% of infections encountered in the intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…Recently, GCxGC-TOF-MS methods were used to discover 28 new P. aeruginosa VOCs as well as confirming 28 former VOCs [86]. This area of research seemed to gain further interest between 2017-2019, since a number of works relating to this topic were published [87][88][89][90][91][92][93]. Most research groups used a metabolite detection approach: GC-MS [87,88], GCxGC-TOF-MS [93], and TD-GC-MS (GC-MS coupled with a thermal desorption, TD, system) [91].…”
Section: Detection Of Urinary Tract Infection Using Volatile Organic mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, GCxGC-TOF-MS methods were used to discover 28 new P. aeruginosa VOCs as well as confirming 28 former VOCs [86]. This area of research seemed to gain further interest between 2017-2019, since a number of works relating to this topic were published [87][88][89][90][91][92][93]. Most research groups used a metabolite detection approach: GC-MS [87,88], GCxGC-TOF-MS [93], and TD-GC-MS (GC-MS coupled with a thermal desorption, TD, system) [91].…”
Section: Detection Of Urinary Tract Infection Using Volatile Organic mentioning
confidence: 99%
“…This area of research seemed to gain further interest between 2017–2019, since a number of works relating to this topic were published [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. Most research groups used a metabolite detection approach: GC-MS [ 87 , 88 ], GCxGC-TOF-MS [ 93 ], and TD-GC-MS (GC-MS coupled with a thermal desorption, TD, system) [ 91 ]. DeJong et al identified E. coli in human urine (simulated infection samples) using surface enhanced Raman spectroscopy [ 92 ].…”
Section: Detection Of Urinary Tract Infection Using Volatile Organmentioning
confidence: 99%
“…Whereas there exists a substantial amount of information regarding soluble factor signaling and juxtacrine signaling mechanisms, much less is known regarding volatile signaling. Principally regarded as a potential diagnostic for identifying bacterial species in vivo (174)(175)(176), volatile chemicals secreted by microbial species perform multiple functions as both symbiotic and antagonistic factors in complex signaling environments (177)(178)(179)(180); indeed, microbial volatile organic compounds (mVOCs) have been described to play an important role in both intra-and inter-kingdom interactions (180). Additionally, these factors can originate from various microbes and kingdoms, and vary based on the microbial makeup of colonies, as well as the morphological form of microbe (i.e., spore vs. filamentous).…”
Section: Volatile Signalingmentioning
confidence: 99%
“…This beneficial effect on growth and resistance is important for infections where there are multiple distal sites of pathogen colonies, as communication between these locations is not limited by the soluble diffusion-or contact-based signaling required for paracrine and juxtacrine signaling, making it more difficult for the host to intercept or impede these signals. However, much is still unknown regarding the detrimental and antagonistic effects of pathogen-derived volatiles on other pathogens in the lungs, as much of the research has focused on either the positive effects of microbial volatile signaling for pathogen survival, or the use of these volatile signals as diagnostics for bacterial colonization and infection (174,175,187).…”
Section: Pathogen-targeted Volatile Signalingmentioning
confidence: 99%
“…Finally, other non-culture based omics approaches such as metabolomics and metatranscriptomics are receiving increasing attention in the CF microbiome field [100][101][102][103], and may represent interesting tools to monitor microbial community composition and viability in vitro as well. To this end, in-depth comparative studies between these non-culture based and culture-based approaches will be essential to determine their suitability to accurately reflect microbial community content and viability before and after antibiotic treatment.…”
Section: Microbial Community Membersmentioning
confidence: 99%